Challenges and ways for pain assessment of children in the primary health care - Alkhuzaie, Hisham Fayiz; Alhabib, Yaqoub Yousef; Alanazi, Aysar Farhan; Ali, Mahmoud Ibrahim; Alqahtani, Abdullah Ali; Noorelahi, Sulafa Khaled; Daiwali, Ibrahim Ghaleb; Alawadh, Fatimah Mohammed; Kashmiri, Mohammed Emad; Alyaseen, Salman Mesfer; Alyaseen, Mohsen Mohammed; Alsulaiman, Ali Abdulmajid; et al. (International Journal Of Community Medicine And Public Health, 2021)
Pain assessment and management have shown great advances in recent decades regarding the treatment protocols and the various assessment approaches that have been developed and validated to specific for pediatric patients. In this literature review, we aim to shed more light on the assessment of pain in pediatric patients and the challenges that healthcare workers might face during the process in primary healthcare centers. In neonates, the crying, require O2 to reach a saturations more than 95%, increasing vitals, expressionless, and sleepless score shows the greatest advantage over other scores (COMFORT and distress for mechanically ventilated neonates), while in infants the face, leg, activity, cancelability, and cry scale shows promising results. In older children, self-reporting by the visual analogue scale should be standardized whenever possible or facial, and behavioral assessment should be used. Assessment of pain in patients with cognitive and intellectual disabilities might be challenging, and therefore, it should be interpreted carefully not to be misdiagnosed, in addition to trying to obtain relevant information from a well-trained accompanying caregiver. Further investigations are needed, however, to standardize these scores and to spread awareness among clinicians and caregivers about the importance of appropriate pain assessment.